2002
DOI: 10.1016/s0735-1097(02)02562-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive therapy for the prevention of restenosis after coronary artery stent implantation (IMPRESS study)

Abstract: In patients with persistently high CRP levels after successful coronary artery stent implantation, oral immunosuppressive therapy with prednisone results in a striking reduction of clinical events and angiographic restenosis rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(84 citation statements)
references
References 28 publications
7
76
0
1
Order By: Relevance
“…25,26 It is well-known that other parameters, such as C-reactive protein (CRP), are predictive of restenosis. In fact, recently the IMPRESS Study 27 showed that high CRP levels 72 hours after successful coronary stenting is predictive of a worse prognosis at 12 months, probably suggesting an additional activation of the inflammatory process within the plaque itself and as a response to injury during coronary stenting. Moreover, CRP level at 48 hours after stent implantation in the carotid arteries was associated with a significantly higher 6-month restenosis.…”
Section: Influence Of Increased Leptin Levels On Restenosis After Cormentioning
confidence: 99%
“…25,26 It is well-known that other parameters, such as C-reactive protein (CRP), are predictive of restenosis. In fact, recently the IMPRESS Study 27 showed that high CRP levels 72 hours after successful coronary stenting is predictive of a worse prognosis at 12 months, probably suggesting an additional activation of the inflammatory process within the plaque itself and as a response to injury during coronary stenting. Moreover, CRP level at 48 hours after stent implantation in the carotid arteries was associated with a significantly higher 6-month restenosis.…”
Section: Influence Of Increased Leptin Levels On Restenosis After Cormentioning
confidence: 99%
“…Although initial studies with glucocorticoids failed to show reduction in postballoon restenosis, 24,25 prolonged immunosuppressive therapy with prednisone was found to reduce in-stent restenosis in high-risk high-Creactive protein patients (IMPRESS study). 26 Thus, systemic immunomodulation effectively suppresses the reparation that leads to neointimal formation in a high-risk "inflammatory" subset of patients. Glucocorticoids suppress both innate and adaptive immunity, with a possible acute stimulatory affect on innate immunity.…”
Section: Danenberg Et Al Liposomal Alendronate Inhibits In-stent Restmentioning
confidence: 99%
“…The confluence of clinical and basic evidence suggests that CRP should predict outcome after vascular intervention. Indeed, several reports have demonstrated a worsened outcome, including high rates of angiographic restenosis, in patients with high pre-procedural CRP levels [6][7][8]. Others however, found no correlation between CRP and restenosis [9][10][11].…”
Section: Introductionmentioning
confidence: 99%